N and P Nutrition of Gmelina arborea Roxb. Seedlings on Latosolic Soil. II: Effects of N and P Fertilizers and their Combinations on Histochemical Properties. - Ogbonnaya, Chuks I (1992)
The effects of different levels of Nand P fertilizers and their combinations an the histochemical properties of Gmelina arborea Raxb. seedlings on latosolic soil were investigated. Four levels (0.00, 9.50, 19.00 and 28.50 g/pot) of N and P were applied in all possibl£ combinations. N was applied as calcium ammonium nitrate (Ca(NH)JI'0) and Pas superphosphate (Ca(HI'0) HP)· Equal dases af N and P (N2P2) produced the longest fibres. Application of N without P increased fibre diameter and fibre lumen size. AU lhe treatments significantly increased fibre wall thickness in relation to Lhe control. AU the treatments reduced coefficient of suppleness and increased runkel ratio in